A review of granulocyte colony-stimulating factor receptor signaling and regulation with implications for cancer - Park, Sungjin David; Saunders, Apryl S.; Reidy, Megan A.; Bender, Dawn E.; Clifton, Shari; Morris, Katherine T. (Frontiers in Oncology, 2022)
GCSFR is a critical regulator of granulopoiesis. This systematic review will summarize the available literature examining the mechanisms that control GCSFR signaling, regulation, and surface expression with emphasis on how these mechanisms may be dysregulated in cancer. This is relevant because multiple studies have shown significant upregulation of GCSFR in a variety of cancers, and the receptor is widely expressed throughout the body in numerous cell types. Experiments with different cancer cell lines from breast cancer, bladder cancer, glioma, and neuroblastoma are used to review the biological function and underlying mechanisms of increased GCSFR expression in the frame of tumor proliferation, migration, and metastasis, primarily acting through the JAK/STAT pathway. While the same defective signal transduction pattern was observed in these cancers, the physiological response of this aberrant signal transduction is organ specific. The lifecycle of the receptor is also reviewed to support future work defining how this signaling axis becomes dysregulated in malignancies.